Readiness of national statistical systems in Asia and the Pacific for leveraging big data to monitor the SDGs. - Albert, Jose Ramon
In September 2015, the world committed to the 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs), which have broad and interconnected social, economic, environmental, and governance aspects. The SDGs constitute a universal call to action with countries setting forth 169 specific, time-bound, and quantifiable targets for 2030 to leave no one behind (United Nations 2015).